Islamism : what it means for the Middle East and the world - Osman, Tarek (United States : Yale University, 2016)
'The book provides useful context as it strives to be comprehensive, considering perspectives from Turkey, Iran, Gulf countries, secularists, and non-Muslim minorities; this analysis of the interplay among various countries in the region is truly fascinating... A helpful and clear introduction.'-Publishers Weekly Publishers Weekly'Writing as a reporter-historian of the highest order, Osman provides a masterly overview one of the most important political currents in the world today.'-Booklist, Starred Review Booklist'Osman admirably captures how the gap between the vision of Islamic supremacy and the reality of Muslim subjugation has fueled in Islamist circles a mixture of anger, nostalgia, and disen--chantment.'-Publisher Synopsis.
Includes bibliographical references (pages 282-292) and index.
Sumbangan Mohamad Taha (2017).
Keywords: Islam and politics; Islamic fundamentalism